Model of Hanging Ball Training on Men's Volleyball Service Ability - Supriyanto Supriyanto; Riki Agustian (Universitas Negeri Semarang, 2023)
This study aims to determine the effect of the Hanging Ball Training Model on the Service Ability of Male Volleyball at PST club Bengkulu City. This study refers to a quantitative research approach and uses quasi-experimental research techniques. The sample in this study were 30 athletes. The sampling technique used was purposive sampling technique. The instrument used was top service test. Based on the results of the study that showed there was a significant effect between hanging ball training on service ability on volleyball at SMPN 2 Bengkulu City, it was proven from t_count = 5.397 > t_table = 2.048 at a significant level = 0.05. with an increase in the percentage of 30.06%, then Ha is accepted.